Hemophagocytic Lymphohistiocytosis Possibly Triggered by Craniotomy Surgery: A Rare Association with Uplifting Ending (Bangladesh Critical Care Journal, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and life-threatening syndrome of excessive inflammationand tissue destruction due to abnormal immune activation. HLH can occur as a familial or sporadic disorder, as wellas can be triggered by a variety of events that disrupt immune homeostasis. In HLH, natural killer cells and cytotoxiclymphocytes fail to eliminate activated macrophages resulting in excessive CD8+ T cell and activation of moremacrophages with highly elevated levels of interferon-gamma and other cytokines, which drive the pathology of HLH.Here, we present a case of 15 years old boy with HLH, which possibly was triggered after surgical intervention forarachnoid cyst in the right parietal lobe. It was a daunting challenge for us to evaluate and diagnose the patientpromptly since he was critically ill and developed pancytopenia, along with grossly altered liver function test andmarkedly raised ferritin in a short period of time. But it was even more crucial to start treatment in the form ofchemotherapy in such a patient who had very severe neutropenia as well as thrombocytopenia.Bangladesh Crit Care J March 2023; 11 (1): 39-42